2017
DOI: 10.18632/oncotarget.14452
|View full text |Cite
|
Sign up to set email alerts
|

A novel microRNAs expression signature for hepatocellular carcinoma diagnosis and prognosis

Abstract: This study aims to identify prognostic microRNAs (miRNAs) biomarkers for diagnosis and survival of hepatocellular carcinoma (HCC) based on large patients cohort analysis. HCC patient cohort data were downloaded from The Cancer Genome Atlas, including paired HCC and adjacent non-cancer tissues. Receiver operating characteristic curve method was used to classify cancer and non-cancer tissues according to microRNAs expression levels. The aberrant microRNAs expression level were ranked and risked for building a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 29 publications
4
66
1
Order By: Relevance
“…Another study by Wang et al (15) indicated that miR-217 promotes the proliferation and invasion of BC by repressing tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein-γ. miR-3677 correlates significantly with the survival time of patients with hepatocellular carcinoma (16)(17)(18). However, the biological function of miR-3677 in BC remains yet to be fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Wang et al (15) indicated that miR-217 promotes the proliferation and invasion of BC by repressing tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein-γ. miR-3677 correlates significantly with the survival time of patients with hepatocellular carcinoma (16)(17)(18). However, the biological function of miR-3677 in BC remains yet to be fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…miR-421 has been regarded as an onco-microRNA in various types of cancers, including neuroblastoma [15,16], gastric cancer [8], lung adenocarcinoma [7], pancreatic cancer [9], hepatocellular carcinoma [5,9], and nasopharyngeal carcinoma [17], etc. It is reported that miR-421 was also upregulated in IBC compared to non-IBC [4].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with those in corresponding non-tumor tissue, miRNA-421 was found to be highly expressed in tissue from hepatocellular carcinoma [5], osteosarcoma [6], lung adenocarcinoma [7], gastric cancer [8], and pancreatic cancer [9]. Furthermore, in patients with hepatocellular carcinoma [5], osteosarcoma [6], or gastric cancer [8], high expression levels of miR-421 were associated with poor prognosis. However, the clinical significance of miR-421 in patients with breast cancer is still to be investigated.…”
mentioning
confidence: 99%
“…In addition, miRNAs regulate their target gene expression, involved in biological processes such as apoptosis, cell cycle regulation, angiogenesis, and metastasis and the miRNAs targeted genes mainly acts as enzyme binding, dehydrogenase, and glutamate transmembrane transporter and so on. 68,69 HCC includes several secondary conditions cirrhosis, viral infection, fibrosis, and inflammation, and miRNA biomarkers being not specific, could have been triggered by any of the above mentioned conditions, which is a caveat in the assessment of using miRNAs in HCC. As multiple miR-NAs target genes, it would be reasonable to select a panel of deregulated miRNAs that can be used as a diagnostic tool in HCC.…”
Section: Role Of Mirnas In Hccmentioning
confidence: 99%